Cost-benefit analysis of rehabilitation and opening new cultivation land for tangerine cv Madu impacted by volcanic ash fallout of Mount Sinabung, North Sumatra, Indonesia - LYLI MUFIDAH; AGUS SUGIYATNO; M. TAUFIQ RATULE (Smujo International, 2017)
Mufidah L, Sugiyatno A, Ratule MT. 2017. Short Communication: Cost-benefit analysis of rehabilitation and opening new cultivation land for tangerine cv Madu impacted by volcanic ash fallout of Mount Sinabung, North Sumatra, Indonesia. Nusantara Bioscience 9: 339-345. Indonesian tangerine plants which have diverse varieties possess the adaptability from lowlands to highlands in the tropical region. Some of the tangerine production centers in Indonesia, such as Karo, Mandailing Natal, Dairi, Malang, Batu, and Bali are located in the volcano path which is prone to eruption. The eruption of Mount Sinabung in 2013 and 2014 had caused damage to the local tangerine cv Madu cultivation which was estimated to reach more than 476 billion rupiahs. The eruption affected a cultivation area of 7.202,89 ha and has been predicted to be one of the factors that caused the decline of North Sumatra’s contribution to tangerine production. Therefore, this paper has tried: (i) to analyze the financial feasibility of rehabilitating tangerine cv Madu cultivation located in between 7-10 km radius of the eruption center (zone 1) and in between 5-7 km radius of the eruption center (zone 2), and (ii) to consider the option of opening up a new tangerine cultivation land.The results showed that the BCR for the immediate rehabilitation of zones 1 and 2 were 3.33 and 2, respectively. Thus, the rehabilitation scheme was feasible to be implemented and can reduce the damage and losses suffered by farmers. On the other hand, the opening of new land still takes approximately three years to be productive. The BCRof the option of opening new land within that period of time was 0.47, which is lower compared with that of the rehabilitation of zones 1 and 2 (2.61 and 2.57, respectively).This study was intended as an initial guidance for making decisions and determining the potential benefit to be gained and the losses that can be avoided. This study also gave an overview of the budget that should be prepared. In conclusion, we recommended the farmers to carry out the rehabilitation over opening up new cultivation land.